Existing food processing classifications overlook the phytochemical composition of processed plant-based protein-rich foods - Raita, Jasmin; Ahmed, Hany; Chen, Kang; Houttu, Veera; Haikonen, Retu; Kårlund, Anna; Kortesniemi, Maaria; Yang, Baoru; Koistinen, Ville; Hanhineva, Kati (NATURE PORTFOLIO, 2025)
According to existing food processing classification systems, plant-based protein-rich (PBPR) foods are often considered 'ultra-processed'-and therefore perceived as unhealthy-despite their ability to provide various bioactive compounds beneficial for human health. Here we used a non-targeted metabolomics approach to analyse the impact of processing on the biochemical composition of PBPR foods. Our results show that existing food classification systems may provide questionable categories for PBPR foods without considering their overall biochemical composition, including phytochemicals. An analysis focusing specifically on biochemical compounds of soy-based products manufactured using various technologies showed no clear distinctions between processing groups in the principal component analysis based on the NOVA and Poti classification. However, clear differences were found between soy-based products based on their phytochemical profile. Although food processing classification systems are welcome in their attempt to guide consumers towards healthy choices, they should be improved to more accurately reflect the biochemical composition of PBPR foods.